Культуровы наслідства акциі «Вісла» для Лемків - Helena Duć-Fajfer (Ksiegarnia Akademicka Publishing, 2018)
Cultural Consequences of Operation ‘Vistula’ for the Lemkos The text is an attempt to emphasize the Lemkos’ perspective in the commemoration of the Operation ‘Vistula’ seventy years after its completion. From this perspective cultural consequences are more important than any other, because being a Lemko as an ethno-cultural category was completely destroyed as a result of the dislocation, and Lemkos were subjected to denationalization. The considerations of this paper have been wrapped around two main threads – the first refers to the ideological connection of the Lemkos with the Ukrainians as victims of the operation “Wisła” to motivate the unity of their identities. In this case, the falsehood and negative effects of such propaganda were shown. The second theme exposes the essence of cultural losses, emphasizing language issues which threaten this group’s existence as a separate ethnos. It is partly based on research on trauma related to dislocation and disappearance of the most important determinants of cultural identity of Lemkos, on statistical data established during the 2002 and 2011 censuses and observations of ethnic behaviors and attitudes in generations of children, grandchildren and great-grandchildren of displaced persons. The examples given and the data show the alarming scale of fragmentation and destruction of the Lemko community seventy years since the ‘Vistula has flowed’, or the strategic denationalization is a kind of threatening message formulated with the framework of the humanities involved.